71.3k views
20 votes
You can find the derivative of the inverse function by differentiating the inverse explicitly, or by using the formula:

User Edcs
by
5.1k points

1 Answer

9 votes

If a function f(x) has an inverse f ⁻¹(x), then by definition


f\left(f^(-1)(x)\right) = x

Differentiating both sides with respect to x yields


f'\left(f^(-1)(x)\right) * \left(f^(-1)\right)'(x) = 1 \implies \left(f^(-1)\right)'(x) = \frac1{f'\left(f^(-1)(x)\right)}

Now, if f(a) = b and b = f ⁻¹(a), then


\left(f^(-1)\right)'(a) = \frac1{f'\left(f^(-1)(a)\right)} = \frac1{f'(b)}

User Renise
by
5.6k points